Relative Age Effect (RAE) in football talents - the role of Youth Academies in transition to professional status in Germany - Grossmann, B.; Lames, M. (International Journal of Performance Analysis in Sport, 2013)
The aim of this study was to investigate the impact of the relative age effect in German football focusing on the role of the RAE in the transition from youth academy to Bundesliga. We examined the RAE of all male and female German youth national teams in 2012, all U17 and U19 Bundesliga teams in 2010/11 and all Bundesliga teams in 2011/12. A RAE was found in every youth national team, in 25 of 42 U19 teams and 41 of 42 U17 teams. In U17 teams, the final rank of the teams correlates with the median: the older the team is, the better is the rank with Spearman's p = .311 and P = .021. Almost half of the players in Germany's top league originate from a German youth academy due to a rule that demands the number of those players being eight or more per team, but also because of the quality of those players. When assessing the transition of youth Bundesliga players, almost twice as many young players make it to professional adult teams than early in the year born athletes. Thus, the selection of players based on their prospects for adult football might be preferential for the German football youth academies.